Office blood pressure values and the necessity of out-of-office measurements in high-risk pregnancies. Issue 9 (September 2019) - Salazar, Martin R.; Espeche, Walter G.; Balbín, Eduardo; Leiva Sisnieguez, Carlos E.; Leiva Sisnieguez, Betty C.; Stavile, Rodolfo N.; March, Carlos; Olano, Ricardo D.; Soria, Adelaida; Yoma, Osvaldo; Prudente, Marcelo; Torres, Soledad; et al.
Abstract : Objectives: To determine if there is an office blood pressure (BP) value below which out-of-office measurements are unnecessary in high-risk pregnant women. Methods: We conducted a prospective cohort study in women in the second half of high-risk pregnancies. Office BP measurements and ambulatory blood pressure monitoring (ABPM) was performed. The cohort was divided according to quartiles of office BP and in normotension, white-coat hypertension, masked hypertension and sustained hypertension. The risks for preeclampsia/eclampsia for each category were estimated. Results: Three hundred seventy-three women (30 ± 7 years with 32 ± 4 weeks of gestation) were included; 69 women (18.5%) developed preeclampsia/eclampsia. Risk for preeclampsia/eclampsia increased in a stepwise manner through quartiles of systolic office BP (8.8, 13.4, 19.6 and 32.3%, P < 0.001) and diastolic office BP (6.5, 13.7, 19.6 and 34, 4%, P < 0.001). OR increased significantly through quartiles of systolic ( P = 0.004) and diastolic ( P < 0.001) office BP; the significance becomes evident between the second and third quartile, the cut-off point between these was 125/76 mmHg. Prevalence of white-coat and masked hypertension were 3.8 and 24.7%, respectively. Using ABPM, 14/61 office hypertensive women were reclassified as white-coat hypertension but 92/312 normotensive women as masked hypertension. OR for preeclampsia/eclampsia increased significantly in women with masked hypertension. Absolute risk for preeclampsia/eclampsia in women with office BP less than 125/75 mmHg was similar than that in women with normal ABPM, 7.2 and 7.1%, respectively. Conclusion: Masked hypertension was a prevalent and high-risk condition. Office BP at least 125/75 mmHg in the second half of gestation seems appropriate to indicate out-of-office measurements in high-risk pregnancies.